Achievements of primary prevention targets in individuals with high risk of cardiovascular disease: an 8-year follow-up of the Tromsø study. Issue 5 (22nd September 2022) - Hagen, Amalie Nilsen; Ariansen, Inger; Hanssen, Tove Aminda; Lappegård, Knut Tore; Eggen, Anne Elise; Løchen, Maja-Lisa; Njølstad, Inger; Wilsgaard, Tom; Hopstock, Laila Arnesdatter
Abstract: Aims: To study change over 8 years in cardiovascular risk, achievement of national guideline-based treatment targets of lipids, blood pressure (BP) and smoking in primary prevention of cardiovascular disease (CVD), medication use, and characteristics associated with target achievement among individuals with high CVD risk in a general population. Methods and results: We followed 2524 women and men aged 40–79 years with high risk of CVD attending the population-based Tromsø study in 2007–08 (Tromsø6) to their participation in the next survey in 2015–16 (Tromsø7). We used descriptive statistics and regression models to study change in CVD risk and medication use, and characteristics associated with treatment target achievement. In total, 71.4% reported use of BP- and/or lipid-lowering medication at second screening. Overall, CVD risk decreased during follow-up, with a larger decrease among medication users compared with non-users. Treatment target achievement was 31.0% for total cholesterol <5 mmol/L, 27.3% for LDL cholesterol <3 mmol/L, 43.4% for BP <140/90 (<135/85 if diabetes) mmHg, and 85.4% for non-smoking. A total of 9.8% reached all treatment targets combined. Baseline risk factor levels and current medication use had the strongest associations with treatment target achievement. Conclusion: We found an overall improvement in CVD risk factors among high-risk individuals over 8 years. However, guideline-based treatment target achievement was relatively low for all risk factors except smoking. Medication use was the strongest characteristic associated with achieving treatment targets. This study has demonstrated that primary prevention of CVD continues to remain a major challenge. Graphical Abstract: Graphical abstract